E-069 Validation of a New Modified Capillary Index Score Angiographic Real Time Assessment of Dead vs Salvable Tissue. (26th July 2014) - Teleb, M; Noufal, M; Sattar, A; Wazni, W; Issa, M; Asif, K; Gheith, A; Castonguay, A; Zaidat, O
Abstract : Background: The original capillary index score publication only included patients that had full digital subtraction angiograms (DSA) before stroke intervention. This CIS was a single center publication with no external validation. Many centers do not perform a full DSA to assess all collaterals before intervention. Hypothesis: A modified capillary index score (mCIS) using only the ICA injection can predict outcome in MCA occlusions (only MCA occlusions included). Objective: Validate the utility and use of a modified capillary index score (mCIS) to assess outcomes and improvement in acute stroke patients. Methods: mCIS was assessed on all consecutive patients with an MCA occlusion with complete database information. NIHSS, recanalization (mTICI), and mRS before and after treatment were assessed. mCIS of 2–3 was considered favorable as per original publication. Correlation between favorable CIS, NIHSS improvement, and mRS (0–3 good) were assessed. Results: 33 patients with MCA occlusion with complete data sets where assessed. 63.6% (21/33) had a favorable mCIS (2–3) and 36.4% had a poor mCIS(0–1). Recanalization of TICI 2b or greater was achieved in 42.9% (9/21) of patients with favorable mCIS and 58.3% (7/12) of patients with poor mCIS. Of those with favorable mCIS 28.6% (6/21) had a good mRS of ≤3 at discharge vs those with poor mCIS while those with a poor mCIS 33.3% had a good mRS at discharge. However, mortality was lower in favorable mCIS vs. poor mCIS (9.5 vs. 33.35, p = 0.09). Conclusions: A modified CIS is did not predict the functional outcome but may be predictor of mortality. Small sample size, lack of long-term follow up, or the lower rate of recanalization of those with favorable mCIS could have contributed to the negative outcome. A prospective or larger study with long term follow up is needed for validation. References: Al-Ali F, Jefferson A, Barrow T, et al . The capillary index score: rethinking the acute ischemic stroke treatment algorithm. Results from the Borgess Medical Center Acute Ischemic Stroke Registry. J Neurointerv Surg. 2013 ; 5 (2):139–143. doi:10.1136/neurintsurg-2011-010146 Capillary Index Score, Baseline Characteristics and Outcomes Favorable mCIS Unfavorable mCIS P Value Baseline NIHSS 14 + /-6.9 18.3 + /-3.9 0.051 Age 64.3 + /-16.6 68.8 + /-4.9 0.453 Good Recanalization (2b-3) 42.9% (9/21) 58.3% (7/12) 0.391 NIHSS at Discharge 10.8 + /-7.5 15 + /-2.5 0.099 NIHSS at Discharge in TICI 2b and higher 5.8 + /-4.2 13.4 + /-13.7 0.067 Mortality 2/21 (9.5%) 4/12 (33.33%) 0.093 Good Outcome (mRS < = 3) 28.6% (6/21) 33.33% (4/12) 0.775 Good Outcome in TICI2b or higher 12 mRS < = 3) 5/9 (55.6%) 4/7 (57.1%) 0.0949 Disclosures: M. Teleb: None. M. Noufal: None. A. Sattar: None. W. Wazni: None. M. Issa: None. K. Asif: None. A. Gheith: None. A. Castonguay: None. O. Zaidat: 2; C; Penumbra, Stryker, Covidie. 3; C; Penumbra, Stryker, Covidien.